Pro-equity immunization and health systems strengthening strategies in select Gavi-supported countries. Issue 17 (22nd April 2021) - Dadari, Ibrahim; Higgins-Steele, Ariel; Sharkey, Alyssa; Charlet, Danielle; Shahabuddin, Asm; Nandy, Robin; Jackson, Debra
Highlights: Gavi-supported countries have implemented a menu of pro-equity immunization strategies. A lot of the strategies addressed social norms, utilization, and coordination issues. Partially vaccinated and 'zero dose' children could be reached with these strategies. The methodology used for this mapping can be applied further to synthesize practices. A publicly available dashboard compiles these strategies for stakeholder access. Abstract: Background: Achieving universal immunization coverage and reaching every child with life-saving vaccines will require the implementation of pro-equity immunization strategies, especially in poorer countries. Gavi-supported countries continue to implement and report strategies that aim to address implementation challenges and improve equity. This paper summarizes the first mapping of these strategies from country reports. Methods: Thirteen Gavi-supported countries were purposively selected with emphasis on Gavi's priority countries. Following a scoping of different documents submitted to Gavi by countries, 47 Gavi Joint Appraisals (JAs) for the period 2016–2019 from the 13 selected countries were included in the mapping. We used a consolidated framework synthesized from 16 different equity and health systems frameworks, which incorporated UNICEF's coverage and equity assessment approach – an adaptation of the Tanahashi model. Using search terms, the mapping was conducted using a combination of manual search and the MAXQDA qualitative analysis tool. Pro-equity strategies meeting the inclusion criteria were identified and compiled in an Excel database, and then populated on a tableau visualization dashboard. Results: In total, 258 pro-equity strategies were implemented by the 13 sampled Gavi-supported countries between 2016 and 2019. The framework determinants of social norms, utilization, and management and coordination accounted for more than three-quarters of all pro-equity strategies implemented in these countries. The median number of strategies reported per country was 17. Afghanistan, Nigeria, and Uganda reported the highest number of strategies that we considered as pro-equity. Conclusion: Findings from this mapping can be useful in addressing equity gaps, reaching partially immunized, and 'zero-dose' vaccinated children, and valuable resource for countries planning to implement pro-equity strategies, especially as immunization stakeholders reimagine immunization delivery in light of COVID-19, and as Gavi finalizes its fifth organizational strategy. Future efforts should seek to identify pro-equity strategies being implemented across additional countries, and to assess the extent to which these strategies have improved immunization coverage and equity.